2022
DOI: 10.3390/ijms23020831
|View full text |Cite
|
Sign up to set email alerts
|

The Anticancer Potential of Doxycycline and Minocycline—A Comparative Study on Amelanotic Melanoma Cell Lines

Abstract: Malignant melanoma is still a serious medical problem. Relatively high mortality, a still-growing number of newly diagnosed cases, and insufficiently effective methods of therapy necessitate melanoma research. Tetracyclines are compounds with pleiotropic pharmacological properties. Previously published studies on melanotic melanoma cells ascertained that minocycline and doxycycline exerted an anti-melanoma effect. The purpose of the study was to assess the anti-melanoma potential and mechanisms of action of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 97 publications
1
6
0
Order By: Relevance
“…Others have shown that A375 cell lines have low MITF mRNA levels at baseline. 31 , 50 Our results also identified genes not previously observed as predicted targets of SOX10 in melanoma, including Sphingosine-1-Phosphate Receptor 2 (S1PR2) and Adhesion G Protein-Coupled Receptor G6 (ADGRG6). Stimulation of S1PR2 inhibits Rac and activates RhoA in B16F10 mouse melanoma cells, reducing migration and invasion.…”
Section: Discussionsupporting
confidence: 71%
“…Others have shown that A375 cell lines have low MITF mRNA levels at baseline. 31 , 50 Our results also identified genes not previously observed as predicted targets of SOX10 in melanoma, including Sphingosine-1-Phosphate Receptor 2 (S1PR2) and Adhesion G Protein-Coupled Receptor G6 (ADGRG6). Stimulation of S1PR2 inhibits Rac and activates RhoA in B16F10 mouse melanoma cells, reducing migration and invasion.…”
Section: Discussionsupporting
confidence: 71%
“…Comparing the calculated EC 50 values for tigecycline with those obtained for doxycycline [ 11 , 33 ] and minocycline [ 12 , 33 ], it can be concluded that the drugs exhibit a similar effect against melanotic melanoma. The values for 72-h incubation of the drugs with COLO 829 cells were as follows: 16.3 µM for doxycycline, 13.9 µM for minocycline, and 19.2 µM for tigecycline.…”
Section: Discussionmentioning
confidence: 95%
“…This creates a unique opportunity to use tetracyclines in the treatment of skin diseases, including melanoma. Previous studies showed the anti-melanoma potential of doxycycline, minocycline, and chlortetracycline [ 11 , 12 , 33 , 34 ]. The obtained results allowed for the conclusion that the activity of tetracyclines against melanoma cells is associated with the inhibition of cell proliferation and the induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Eravacycline was ranked 17th out of the 1371 ranked molecules. We gave the drug higher priority due to the known anti-cancer activity of tetracyclines [ 25 ] and its commercial availability.…”
Section: Resultsmentioning
confidence: 99%